Ungkapan Bermakna Budaya dalam Adat Perkawinan - kusnan, Kusnan (Kajian Linguistik, 2015)
Theproblem of this research is 1) what the expressions forms of mesarapu, mesokei,and umo’api in the marriage custom of Tolaki Tribe in South East of Sulawesiare. 2) What the meaning of the cultural expressions of mesarapu, mesokei, andumo’api in the marriage custom in Tolaki-South East Sulawesi are.This research is a qualitative descriptiveresearch. Data used in this research is language expressions of mesarapu,mesokei, and umo’api which collected through 1) deep interview, 2) observationin the field in order to get the detail data, and 3) library research in orderto get the personal writings, publishing documents, or research result fromlocal instances or local culture institutions. Data in this research iscollected through 1) recording technique which collecting data is got frominformant using recording tools. 2) Note taking which is used to record otherexternal additional and important data. 3) Transcript technique which is thetransforming data from spoken language to written language. 4) Translationtechnique which is transforming expressions in mesarapu, mesokei, and umo’apiwhich are in Tolaki language into Indonesian Language. Analysis of the meaning in this research isused descriptive interpretative approach using the concept of SPEAKING, then isanalyzed in accordance to the purpose of this research. The researcherdescribed the data based on Hymes concept, the existing data is chosen orexerted according to the verbal expressions and non verbal expressions. Nonverbal expressions are the data used in the marriage custom of Tolaki Tribe inSouth East Sulawesi. The data collected is the language expressions of  mesarapu, mesokei and umo’api in the marriagecustom of Tolaki Tribe in South East Sulawesi which is classified by Chaer(2002:75). The result of this researchshows that the language expression of mesarapu, mesokei, and umo’api in themarriage custom of Tolaki Tribe is the form of communication media which isfull of meaning. The language expression of mesarapu, mesokei, and umo’api withimplicit language and symbolic language which meaning cannot be reached by somepeople.Key words: expressions ofmesarapu,mesokei, and umo’api, and cultural meaning